Perbedaan Tingkat Kejadian Karies Pada Anak Berkebutuhan Khusus Berdasarkan Jenis Kelamin Di Kelas 1-4 SDLB Widya Mulya, Pundong, Bantul, DIY - Krisna Adhi, Yudhanto; Octavia, Alfini (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2013)
Background.Oral health in children with special needs, usually need more treatment than those in normal. This is going to get worse if their parents have lack of knowledge and attention. Commonly in our society children with special needs is still considered as a second class civil. This circumstance could inhibit their growth, development and potency. Purpose. The purpose of this study is to know the difference of caries index level between boys and girls in grades 1-4 SDLB using caries index def - t and DMF - T. Methods.This study has been done to 22 student of 1-4 grades of Widya Mulya, Pundong, Bantul, DIY. Subjects consisted of 12 boys and 10 girls. The method was observational with cross sectional design. When the subjects were examined, the caries index( def-t and DMF-T) has recorded with odontogram sheet. The the severity of caries between boys and girls was compared. Result. The score of def-t in boys 1-4 grades are 4,33 and the girls 3,2. The score ofDMF-T in boys 3 and the girls 3,2. Conclusion. The result of this research was found that the caries index between boys and girls SDLB 1-4 graders at Widya Mulya, Pundong, Bantul, DIY was not different significantly